Price Dynamics Unveiled: A Comparative Study on Pre-Sale, On-Sale, and Post-Sale Day Prices on Amazon - Mansi Walke; Niraj Singh Tomar; Gunjan Ghanwat; Manohar Kapse; Vinod Sharma (Australasian Accounting, Business and Finance Journal, 2025)
This study investigates the authenticity of price reductions during sales events on Amazon by analysing the price dynamics of products before, during, and after the sale. The primary objective is to evaluate whether the advertised discounts genuinely translate into significant consumer savings. By comparing pre-sale prices with on-sale and post-sale day prices, the research aims to offer a macro-level perspective on the actual impact of these discounts. It calculates the percentage change in the aggregate price of products to reveal overarching trends in pricing strategies. Furthermore, the study delves into individual product pricing to identify instances of both price reductions and increases, uncovering variations in pricing tactics. This granular analysis highlights discrepancies between perceived and actual discounts, providing valuable insights into the effectiveness and transparency of Amazon's sales strategies. The findings enhance consumer awareness and contribute to the broader discourse on e-commerce pricing ethics and practices.
Keywords: Amazon; Price Dynamics; Sale Events; Real Discounts; Price Reductions; Pre-Sale; On-Sale; Post-Sale Prices; Pricing Analysis.